Técnicas lúdicas y su relación con el aprendizaje de las matemáticas de los estudiantes de la escuela de educación básica Guillermo Arosemena Coronel durante el periodo lectivo 2015 – 2016. - Vaca Macias, Jessica Yesenia (2016)
In the research carried out at the Guillermo Arosemena Coronel School of Basic Education, the objective is to propose viable strategies that favor the inclusion of play activities in the educational programs of teachers, so that the learning process of students is more attractive And significant, through an orientation workshop and the practice of the different leisure activities for the teaching staff of the establishment, highlighting the importance and the benefits they present, for students and for teachers, where achievement is facilitated Of the learning competences. The final report allowed us to recognize the importance of play activity as a pedagogical tool to strengthen learning in children, with learning being a process in which the individual appropriates knowledge in its different dimensions, focuses the intervention towards the acquisition of Habits and development of activities motivating children's learning, from the preschool classroom. It is for this reason that the playfulness is not only important for the physical and communicative development, but also contributes to the expansion of needs and that can also be used as a principle of learning in a significant way.